2017
DOI: 10.1007/s00192-016-3253-8
|View full text |Cite
|
Sign up to set email alerts
|

Labia minora hypertrophy: causes, impact on women’s health, and treatment options

Abstract: We generally advise against surgical treatment of labia minora, especially in young, pre-pubertal girls, unless specific medical conditions are also present and/or the psychological impact on the patient is deemed particularly negative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 47 publications
0
6
0
2
Order By: Relevance
“…The size of the labia changes over time, with the most signi cant increase during puberty, and can reportedly be increased with external stimuli such as stretching with weights (24-26). It has been reported that in some African countries, the labia minora can reach 20 cm in size with direct manipulation (24). Other causes of hypertrophy include androgenic hormone exposure in infancy, sensitivity to topical estrogen, dermatitis secondary to urinary incontinence, vulvar lymphedema, and myelodysplastic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the labia changes over time, with the most signi cant increase during puberty, and can reportedly be increased with external stimuli such as stretching with weights (24-26). It has been reported that in some African countries, the labia minora can reach 20 cm in size with direct manipulation (24). Other causes of hypertrophy include androgenic hormone exposure in infancy, sensitivity to topical estrogen, dermatitis secondary to urinary incontinence, vulvar lymphedema, and myelodysplastic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…As hypertrophy of the labia minora is not a disease [ 12 ], the surgical indications are mainly set by the patient’s requirements and expectations. Prior to the procedure, the surgeon should counsel the patient regarding the shape of the patient’s labia minora, clitoris prepuce, and vulva [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The popularity of female genital plastic surgery is gradually rising, and so is labiaplasty (1). Enlarged labia minora could cause functional, cosmetic, and psychosocial issues (2).…”
Section: Introductionmentioning
confidence: 99%